IMPLEMENTING INSTRUCTIONAL SYSTEM DESIGN BETWEEN TAIWAN AND INDONESIA VIA ONLINE TEACHING - Rachmawati, Yeni; Lu, Cheng-Hsiung; Chen, Hui-Hua; Setiasih, Ocih; Kurniawati, Leli (UPI Press, 2014)
The purpose of this study is to share information about the necessity of multicultural educationÂ in Indonesia through online teaching held at National Dong Hwa University, Taiwan, andÂ Indonesia University of Education, Indonesia. As multicultural education will help studentscreate equal educational opportunities from diverse racial, ethnic, social-class, and culturalÂ groups, one of its important goals is to help all students acquire the knowledge, attitudes,Â and skills needed to function effectively in a pluralistic democratic society and to interact, negotiate, and communicate with people from diverse groups in order to create a civic andÂ moral community that works for the common good. This study has implemented â€œDick, CareyÂ Carey modelâ€ through online teaching approach. This research involved one male and fourteen female of fourth semester undergraduate students majoring in Early ChildhoodÂ Teacher Education at Indonesia University of Education. The results may not be generalizedÂ to other teaching institutions due to the limited number of the participants. This research was conducted in the Department of Curriculum Design and Human Potentials, National Dong HwaÂ University, Taiwan and in the Department of Early Childhood Teacher Education, Faculty ofÂ Education, Indonesia University of Education. The distance between Taiwan and Indonesia, limitation of the media, tools and internet connection did not affect the learning process as longÂ as the teacher prepared the needed materials. Online teaching could achieve good improvement,Â similar to traditional teaching using â€œface-to-faceâ€ situation. By using Dick, Carey Careyâ€™sÂ instructional system design, students were able to enhance their understanding about this themeÂ of learning. This condition showed the increase of studentsâ€™ performance mean scores fromÂ 5.142 to 8.928 with four students able to get posttest scores 100% correct, seven students 90%Â correct, two students 80% correct, and only one student 60% correct. According to the percentageÂ of the average score of posttest, the teaching activity by using this approach has succeeded toÂ improve the studentsâ€™ understanding about multicultural education. In addition, the percentage ofÂ each item has increased as well. The comparison between pre- and post-test has shown that theÂ lowest score on pretest was 2.0 and the highest one was 7.0. The result has dramatically increasedÂ on the posttest scores with the lowest score 6.0 and the highest score 10. The rising scores rangedÂ between 2-6 scores with an average of 3.785 point. Consequently, the online teaching by adoptingÂ Dick, Carey Careyâ€™s ISD model has improved studentâ€™s learning performance.